2018
DOI: 10.1007/s00394-018-1611-7
|View full text |Cite
|
Sign up to set email alerts
|

Coffee with a high content of chlorogenic acids and low content of hydroxyhydroquinone improves postprandial endothelial dysfunction in patients with borderline and stage 1 hypertension

Abstract: Purpose The purpose of this study was to evaluate acute effects of coffee with a high content of chlorogenic acids and different hydroxyhydroquinone contents on postprandial endothelial dysfunction. Methods This was a single-blind, randomized, placebo-controlled, crossover-within-subject clinical trial. A total of 37 patients with borderline or stage 1 hypertension were randomized to two study groups. The participants consumed a test meal with a single intake of the test coffee. Subjects in the Study 1 group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 50 publications
(93 reference statements)
0
52
0
1
Order By: Relevance
“…In addition, CGA also has anti-atherosclerotic properties [ 21 ]. A single-blind, randomized, placebo-controlled, crossover trial showed that a single intake of CF with a high content of CGA and a low content of hydroxyhydroquinone, which oxidizes CGA and reduces its function, improved postprandial endothelial dysfunction by decreasing oxidative stress [ 22 ]. A recent meta-analysis of randomized clinical trials reported the antihypertensive effect of CGA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CGA also has anti-atherosclerotic properties [ 21 ]. A single-blind, randomized, placebo-controlled, crossover trial showed that a single intake of CF with a high content of CGA and a low content of hydroxyhydroquinone, which oxidizes CGA and reduces its function, improved postprandial endothelial dysfunction by decreasing oxidative stress [ 22 ]. A recent meta-analysis of randomized clinical trials reported the antihypertensive effect of CGA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coffee with high chlorogenic acid and low hydroxyhydroquinone content (but not coffee with high chlorogenic acid and hydroxyhydroquinone content or placebo coffee), improved postprandial endothelial function with decreased 8-isoprostane levels in plasma. Kajikawa et al, 2019 Healthy subjects, males (N = 17), aged 24-26 years.…”
Section: Martínez-lópez Et Al 2019mentioning
confidence: 99%
“…The mechanism of the beneficial effect of chlorogenic acid was associated with the production of NO and induction of heme oxygenase-1 [ 94 ]. Consumption of coffee with a high content of chlorogenic acids repaired endothelial dysfunction by decreasing oxidative stress [ 95 ]. A previous study indicated that oxidative stress has been demonstrated to play a important role in the development of endothelial dysfunction [ 96 ].…”
Section: Chlorogenic Acid and Metabolic Syndrome Associated-endothmentioning
confidence: 99%